How Valid are Patient Reports of Family History of Illness? - Harris, Rachel; Margaret, W. Linn; Hunter, Kathleen (Methods of Information in Medicine, 1980)
The recall rate of patients’ family medical histories was studied in 200 cancer and non-cancer patients. Data on age and cause of death for parents and grandparents were collected. Although most patients knew the age and cause of death of parents, less than half knew for grandparents. Cancer patients had significantly greater recall for maternally related relatives. A subsample of patients’ family medical histories was compared to death certificate data. Patients’ reports were found to be highly inaccurate. Since only a small subgroup could provide medical history data for grandparents, the generaliz-ability for history of family illness is questioned.
Keywords: Family History; Patient Reports; Validity; Cancer